PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR PELABUHAN PERIKANAN SAMUDERA KENDARI - Darton Darton; Sri Wiyati Mahrani; Ansir Ansir; Aidin Hudani Awasinombu; Rachmat Rialdi Hasan (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
This study aims (1) to determine the effect of transformational leadership and work motivation on employee performance at the ocean kendari fishing port office, (2) to determine the effect of transformational leadership influence on employee performance at the kendari ocean fishing port office, (3) to determine the effect of motivation work on employee performance at the Kendari Ocean Fishery Port Office. The object of this research is the employee at the Kendari Ocean Fishery Port Office. The population in this study were employees at the Kendari Ocean Fishery Port office, amounting to 80 people, because the population was less than 100 people, the sample of this study was 80 office employees at the Kendari Ocean Fishing Port as respondents. The research data was collected using a questionnaire, the research data was analyzed using Multiple Linear Regression through SPSS 21 software. The results of this study (1) Simultaneously transformational leadership and work motivation have a positive and significant effect on employee performance at the ocean kendari fishing port office, (2) transformational leadership has a positive and significant effect on employee performance at the kendari ocean fishing port office, (3) motivation Work has a positive and significant effect on employee performance at the Kendari Ocean Fishery Port Office.